Women specialist managers in Australia – Where are we now? Where to next?. (September 2021) - Westcott, Mark
Management as an occupation has become increasingly feminised in Australia over the last two decades. This article focuses specifically on specialist managers, answering the question of where we are now in terms of gender equity. It charts the increasing but uneven growth of women's employment among specialist management occupations. Women remain concentrated into a relatively small number of management specialisations and it is argued that there is a gendering of certain management roles which is reflected in the value attached to these roles. Using data sourced from the Australian Tax Office, the article shows that men earn higher income across all specialist management groups, including those that are highly feminised, and higher salary across all specialisations excepting one – childcare directors. Evidence is presented detailing the relativities between management specialisations, showing a variation between men and women in terms of rank. Women are much less valued in some management specialisations, such as finance. Men are much less valued in others, such as childcare. The article concludes by speculating how greater gender equity can be achieved among specialist managers but observes that 'management' and 'male' are still tightly connected.